The importance of educational training for the work of educational counselors in schools - Fatah, Dr. Rahman Rasul (Sulaimani Journal for Humanities, 2026)
Educational training has a prominent place in administrative activities that aim to increase production efficiency, develop services and improve performance. To achieve the objectives of this study, the importance of educational training for educational counselors in schools In the field of training in order to achieve a competitive advantage for education in educational institutions in the Kurdistan Region.
Keywords: Educational Training; Educational Instructor; School